Dynamic intramedullary crosspinning technique for the treatment of distal femoral metaphyseal fracture in a free-ranging jaguarundi (Herpailurus yagouaroundi) - Cassanego, Guilherme Rech [UNESP]; Rahal, Sheila Canevese [UNESP]; Alievi, Marcelo Meller; Vaccarin, Charline Vanessa; De Nardin Peixoto, Gabriella [UNESP] (Wiley, 2024)
An approximately 3-month-old female free-ranging jaguarundi (Herpailurus yagouaroundi) was admitted for evaluation of swelling near the right stifle and inability to use the right hindlimb. Radiographic examination revealed a closed, short oblique fracture of the right distal femoral metaphysis, and the bone cortex appeared thin. Because of the poor body condition, the surgical procedure was performed 6 days after admission. The fracture was stabilised using a dynamic intramedullary crosspinning technique. Two 1.5 mm diameter Kirschner (K) wires were introduced at an approximately 20° angle to the sagittal plane of the femur. Radiographic evaluation 3 months after surgery revealed an open distal physis, fracture healing in the remodelling phase and K-wires engulfed by the bone, which made removal impossible. At the 6-month follow-up, a length discrepancy of 0.8 cm in the right femur compared to the left femur was noted. Despite this complication, the locomotion pattern was considered normal according to visual gait analysis.
Keywords: fracture management; surgery; treatment; wildlife